(untitled) - Kiritani, Elizabeth (Japan, 1995)
This book introduces about on the street, housing and interiors, artisans and crafts, festivals and events, seasonal customs, daily life, entertainment.
Keywords: Handicraft,Thủ công,Japan,Nhật Bản; Culture,Văn hoá; Japan,Nhật Bản